Divorce in the Digital Era: Legal Analysis of Divorce via WhatsApp in the Perspective of Fiqh and Indonesian Positive Law - Mukharom Mukharom; Sugianto Sugianto; Wasman Wasman; Didi Sukardi (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to analyze the phenomenon of divorce carried out throughdigital communication media, especially the WhatsApp application, fromthe perspective of fiqh and positive Indonesian law. Along with thedevelopment of information technology, many couples have broken offtheir marital relationship through text messages, which raises questionsabout the legal validity of talaq carried out through the media. In fiqhstudies, talaq via WhatsApp is considered valid by some scholars if it meets the requirements of clear intentions and deliberate delivery. However, there is an opinion that direct interaction is more recommended. In Indonesia's legal system, divorce must be processed through religious court procedures to be considered legally valid. At the same time, talaq carried out via WhatsApp has not been explicitly regulated in the applicable laws and regulations. The study also identified the legal impact of digital divorce, including the difficulties faced by individuals who divorce without a court decision, such as the inability to prove divorce status and difficulties in remarriage. Based on these findings, the study recommends regulatory updates regarding digital divorce and the need for public legal education on divorce procedures in Indonesia.